2004
DOI: 10.1158/1078-0432.ccr-04-1393
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol Inhibits Hypoxia-Inducible Factor 1α, Tumor Growth, and Angiogenesis and Augments Paclitaxel Efficacy in Head and Neck Squamous Cell Carcinoma

Abstract: Purpose: Head and neck squamous cell carcinomas have been reported to overexpress hypoxia-inducible factor (HIF)-1␣, a transcription factor that promotes expression of angiogenesis factors and resistance to programmed and therapy-induced cell death. 2-Methoxyestradiol (2ME2) is a natural compound with HIF-1␣ inhibitory activity that is currently being evaluated in phase 1 and 2 clinical trials for advanced solid tumors and multiple myeloma. To our knowledge, this is the first study to evaluate the effects of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 34 publications
7
109
0
Order By: Relevance
“…It has also been reported that 2-ME 2 decreases nuclear binding activity of HIF-1␣ in head and neck squamous cell carcinoma. 69 In the present study, we showed for the first time that 2-ME 2 inhibits the in vivo expression of HIF-1␣-inducible genes VEGF, Glut-1, and PGK as measured by real-time PCR during the first few hours after transplantation. These results are supported by our findings that HIF-1␣ was also reduced in endometriotic tissues at the protein level.…”
Section: Discussionmentioning
confidence: 48%
“…It has also been reported that 2-ME 2 decreases nuclear binding activity of HIF-1␣ in head and neck squamous cell carcinoma. 69 In the present study, we showed for the first time that 2-ME 2 inhibits the in vivo expression of HIF-1␣-inducible genes VEGF, Glut-1, and PGK as measured by real-time PCR during the first few hours after transplantation. These results are supported by our findings that HIF-1␣ was also reduced in endometriotic tissues at the protein level.…”
Section: Discussionmentioning
confidence: 48%
“…Unfortunately, very few data sets exist that allow tumors to grow large enough in order to get a proper estimate of the carrying capacity. We specifically sought out data sets that included data for large populations in order to properly compare the former two models with the latter three (Fujiwara et al, 1993;Takahashi et al, 1992;Murgo, 1985;Richmond et al, 1983;Kisfalvi et al, 2009;Reinmuth et al, 2002;Nakata et al, 1998;Caltagirone et al, 2000;Ricker et al, 2004).…”
Section: Ode Tumor Growth Modelsmentioning
confidence: 99%
“…For example, Li et al (2006a,b) showed that the knockdown of HIF-1 α in breast carcinoma cells repressed G 0 /G 1 -phase accumulation and relieved S-phase block, thereby increasing sensitivity to chemotherapy and attenuating tumor growth (Li et al , 2006a,b ). Functional interference with HIF-1 α in various tumor cells has been shown to result in enhanced cell death upon treatment with chemotherapeutic agents (Ricker et al , 2004 ;Peng et al , 2006 ;Hao et al , 2008 ;Sermeus et al , 2008 ;Flamant et al , 2010 ). However, experimentally increasing HIF-1 α enhanced therapy resistance (Ji et al , 2006 ;Martinive et al , 2006 ).…”
Section: Targeting Hif To Improve Cancer Therapymentioning
confidence: 99%